Resilience and disposition towards critical thinking in students of a private university in Metropolitan Lima - Cieza-Guevara, Liliana (2020)
The purpose of this research was to determine the relationship between resilience and the disposition towards critical thinking in university students. The study corresponded to the descriptive level, of substantive type and with correlational design. The sample consisted of 301 students from different faculties, of both sexes, between 17 and 25 years of age. In the data collection, the Resilience Scale (ER) of Wagnild and Young was applied, a version adapted by Angelina Novella in 2002 and the Scale of readiness towards critical thinking elaborated by Escurra and Delgado (Instrument built under Samejima's model from the conceptual structure developed by Facione and Facione, 1995). The results confirmed the hypothesis, that there is a significant relationship between the resilience and the disposition to critical thinking in students from a private university in Metropolitan Lima, when relating each dimension of resilience, a moderate correlation was found between the dimensions of resilience: self-reliance, perseverance and existential aloneness with the disposition to critical thinking; while the dimension of equanimity and meaningfulness, achieved low correlation. Other results found were that students reached high levels in both variables, and that there are no differences between the dimensions of resilience and disposition to critical thinking considering sex and professional career.